Isolated Cerebellar Involvement in Vitamin B12 Deficiency: A Case Report. (November 2014) - Chakrabarty, Biswaroop; Dubey, Rachana; Gulati, Sheffali; Yoganathan, Sangeetha; Kumar, Ajay; Kumar, Atin
Deficiency of vitamin B12 causes megaloblastic anemia and nervous system demyelination. Structures affected in the nervous system include spinal cord, cranial and peripheral nerves, and brain white matter. A 9-year-old boy presented with knuckle hyperpigmentation and oral ulcers for 3 years, pallor and easy fatigability for 6 months, gait abnormalities for 3 months, and abnormal speech and behavioral abnormalities for 3 days. On examination, he had physical signs of megaloblastic anemia, mood swings with intermittent hallucinations, and features of cerebellar impairment. Blood investigations revealed megaloblastic anemia, and pernicious anemia was ruled out. Brain magnetic resonance imaging (MRI) revealed bilateral cerebellar signal changes. He received treatment for vitamin B12 deficiency and appropriate nutritional counseling. Three months later, he showed significant clinical and radiologic resolution. To our knowledge, isolated cerebellar involvement as the sole neurologic manifestation of vitamin B12 deficiency has not been described previously in children.